Comparison of two analyzer measurements focusing on material stiffness among normal, treatment-naïve, and treated glaucoma eyes - Shuichiro Aoki; Ryo Asaoka; Yuri Fujino; Shunsuke Nakakura; Hiroshi Murata; Yoshiaki Kiuchi (Scientific Reports, 2023)
Abstract To investigate differences in biomechanical properties focusing on stiffness parameters between normal, treatment-naïve primary open-angle glaucoma (POAG), and treated POAG eyes. Retrospective case–control study, This study included 46 treatment-naïve POAG eyes, 46 POAG eyes treated with prostaglandin analogues, and 49 normal eyes used as controls; matched in terms of age and axial length. Corneal hysteresis (CH) and corneal resistance factor (CRF) were measured using an ocular response analyzer (ORA). Fifteen biomechanical parameters were measured with the Corneal Visualization Scheimpflug Technology (Corvis ST), including biomechanical glaucoma factor (BGF) and two stiffness parameters of ‘SP A1’ and ‘stress–strain index (SSI)’, which were compared among the three groups. Additionally, the area under the curve (AUC) values of the receiver-operating curve to discriminate control and treatment-naïve POAG eyes were calculated for BGF and CH. Treatment-naïve POAG eyes had higher ‘SSI’ than normal eyes even after controlling for IOP (p < 0.05, Tukey-Cramer test). Treated POAG eyes had significantly lower CRF, and higher BGF than treatment-naïve POAG eyes. There were also significant differences in CH or SP A1 among the three groups. BGF and CH had similar AUC values (0.61 and 0.59). Treatment-naïve POAG eyes had stiffer corneas compared to normal eyes, which seemed to result from the material/structure of the cornea rather than higher intraocular pressure. Antiglaucoma topical medication alters biomechanical properties measured with Corvis ST. These results are important for understanding the pathogenesis and improving the management of POAG.